Prevalence Of Ocular Morbidities Among School Children in Rural Area of North Maharashtra in India - Deshpande , Jayant D; Malathi , K (National Journal of Community Medicine, 2011)
The global initiative for the Elimination of Avoidable Blindness sets a major challenge to work relentlessly to avoid the preventable blindness. Effective methods of vision screening in school children are useful in detecting correctable causes of decreased vision. Present study was conducted with the objective of estimating the prevalence of ocular morbidity among school children in rural area. A cross sectional study was conducted among school going adolescents studying from 5th to 10th standard in the age group 10-16 years in rural area. The ocular examination of school children was done at the respective schools. All the data obtained was analyzed using the software StatistiXL version 1.8. Chi square test was used to observe the association of the ocular morbidities with respect to age, sex, education of father, occupation, class, and nutritional status. Prevalence of ocular morbidities was found to be 27.65 %. Refractive errors and Vitamin A deficiency were the most common ocular disorders. The prevalence of ocular morbidity showed significant association with socio-economic status (χ2=29.8, p<0.001), education and occupation of parents, while no significant association was found between ocular morbidity and sex of the school children (χ2=0.162, p=0.687), family type (χ2=2.41, p=0.121), and religion (χ2=6.77, p=0.08) of the school children. Nutritional status of children was significantly associated with the occurrence of ocular morbidity. High prevalence of ocular morbidity among school children in rural area was observed. Periodic screening of school children is very essential to improve the quality of eye-sight.